"I Know Who I Am; the Real Me, and That Will Come Back": The Importance of Relational Practice in Improving Outcomes for Carers of People With Dementia. (April 2020) - MacBride, Tamsin; Miller, Emma; Dewar, Belinda
Effective support to carers of people with dementia can be critical to maintain quality of life for people with dementia and their families and to sustain the future of health and care systems. Qualitative interviews were undertaken with 14 carers of people with dementia across Scotland, and the data were analysed to identify the outcomes important to the carers. The importance of relationships emerged as the core theme, including relationship with the person with dementia, family members, other carers, and professionals. Although not evident in the literature, the authors noted that the concept of self-relationship was important to carers in the context of changing relationships with others. A multilayered approach to understanding relationships, and an approach to engagement that enables carers to define and express their priorities, is necessary to fit with the relational nature of care.